Clueless McGee and the inflatable pants - Mack, Jeff (Mack, Jeff. Clueless McGee, 2013)
Fifth-grader PJ "Clueless" McGee writes a series of letters to his father, a private investigator, telling of his attempt to learn who stole the science fair trophy, thus clearing his own name.